Closing the Gender STEM Gap - A Large-Scale Randomized-Controlled Trial in Elementary Schools - Kerstin Grosch; Simone Haeckl; Martin G. Kocher (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine individual-level determinants of interest in STEM and analyze whether a digital web application for elementary-school children can increase children's interest in STEM with a specific focus on narrowing the gender gap. Coupling a randomized-controlled trial with experimental lab and survey data, we analyze the effect of the digital intervention and shed light on the mechanisms. We confirm the hypothesis that girls demonstrate a lower overall interest in STEM than boys. Moreover, girls are less competitive and exhibit less pronounced math confidence than boys at the baseline. Our treatment increases girls' interest in STEM and decreases the gender gap via an increase in STEM confidence. Our findings suggest that an easy-to-implement digital intervention has the potential to foster gender equality for young children and can potentially contribute to a reduction of gender inequalities in the labor market such as occupational sorting and the gender wage gap later in life.
Keywords: C93; D91; I24; J16; J24; 330; STEM; digital intervention; gender equality; field experiment